Acute differences in foot strike and spatiotemporal variables for shod, barefoot or minimalist male runners. - MCCALLION, PHILIP (My University, 2014)
This study compared stride length, stride frequency, contact time, flight time and foot-strike patterns (FSP) when running barefoot, and in minimalist and conventional running shoes. Habitually shod male athletes (n = 14; age 25 ± 6 yr; competitive running experience 8 ± 3 yr) completed a randomised order of 6 by 4-min treadmill runs at velocities (V1 and V2) equivalent to 70 and 85% of best 5-km race time, in the three conditions. Synchronous recording of 3-D joint kinematics and ground reaction force data examined spatiotemporal variables and FSP. Most participants adopted a mid-foot strike pattern, regardless of condition. Heel-toe latency was less at V2 than V1 (-6 ± 20 vs. -1 ± 13 ms, p < 0.05), which indicated a velocity related shift towards a more FFS pattern. Stride duration and flight time, when shod and in minimalist footwear, were greater than barefoot (713 ± 48 and 701 ± 49 vs. 679 ± 56 ms, p < 0.001; and 502 ± 45 and 503 ± 41 vs. 488 ±4 9 ms, p < 0.05, respectively). Contact time was significantly longer when running shod than barefoot or in minimalist footwear (211±30 vs. 191 ± 29 ms and 198 ± 33 ms, p < 0.001). When running barefoot, stride frequency was significantly higher (p < 0.001) than in conventional and minimalist footwear (89 ± 7 vs. 85 ± 6 and 86 ± 6 strides·min(-1)). In conclusion, differences in spatiotemporal variables occurred within a single running session, irrespective of barefoot running experience, and, without a detectable change in FSP. Key pointsDifferences in spatiotemporal variables occurred within a single running session, without a change in foot strike pattern.Stride duration and flight time were greater when shod and in minimalist footwear than when barefoot.Stride frequency when barefoot was higher than when shod or in minimalist footwear.Contact time when shod was longer than when barefoot or in minimalist footwear.Spatiotemporal variables when running in minimalist footwear more closely resemble shod than barefoot running.
PUBLISHED
Keywords: male runners